Analisis Peran Pemerintah dalam Pengembangan Pariwisata Pantai Tanjung Tihu, di Kota Gorontalo - Alexander H. Badjuka; Sabrina Meamogu; Siti Rukiah Yusup; Berlian Langoni; Riyan Mananu (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Tourism development has become one of the strategic sectors in encouraging regional economic growth and improving community welfare. Tanjung Tihu Beach in Gorontalo City possesses considerable tourism potential due to its coastal scenery, marine resources, and natural attractiveness. However, the optimization of tourism development cannot be separated from the active role of the government as regulator, facilitator, and catalyst in supporting sustainable tourism management. This study aims to analyze the role of the government in the development of tourism at Tanjung Tihu Beach, Gorontalo City. The research employed a qualitative descriptive approach using a literature review method by examining scientific journals, books, and relevant publications from 2020 onward. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the government has carried out several important roles through infrastructure development, tourism promotion, community empowerment, and collaboration with related stakeholders. Nevertheless, several challenges remain, including limited supporting facilities, inadequate accessibility, weak tourism promotion, and the lack of optimal environmental management. In addition, community participation in tourism management still requires strengthening to support sustainable tourism development. The study concludes that the government’s role in tourism development at Tanjung Tihu Beach has shown positive progress, although improvements in policy implementation, infrastructure quality, digital tourism promotion, and community-based tourism management are still necessary to enhance tourism competitiveness and local economic welfare.